Case report: JAK inhibition as promising treatment option of fatal RVCLS due to TREX1 mutation (pVAL235Glyfs*6) - Friederike Ufer; Susanne M. Ziegler; Marcus Altfeld; Manuel A. Friese (Frontiers in Neurology, 2023)
IntroductionAutosomal dominant mutations in the C-terminal part of TREX1 (pVAL235Glyfs*6) result in fatal retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations (RVCLS) without any treatment options. Here, we report on a treatment of a RVCLS patient with anti-retroviral drugs and the janus kinase (JAK) inhibitor ruxolitinib.MethodsWe collected clinical data of an extended family with RVCLS (TREX1 pVAL235Glyfs*6). Within this family we identified a 45-year-old woman as index patient that we treated experimentally for 5 years and prospectively collected clinical, laboratory and imaging data.ResultsWe report clinical details from 29 family members with 17 of them showing RVCLS symptoms. Treatment of the index patient with ruxolitinib for >4 years was well-tolerated and clinically stabilized RVCLS activity. Moreover, we noticed normalization of initially elevated CXCL10 mRNA in peripheral blood monocular cells (PBMCs) and a reduction of antinuclear autoantibodies.DiscussionWe provide evidence that JAK inhibition as RVCLS treatment appears safe and could slow clinical worsening in symptomatic adults. These results encourage further use of JAK inhibitors in affected individuals together with monitoring of CXCL10 transcripts in PBMCs as useful biomarker of disease activity.